2015
DOI: 10.1002/acn3.260
|View full text |Cite
|
Sign up to set email alerts
|

Pioglitazone regulates myelin phagocytosis and multiple sclerosis monocytes

Abstract: ObjectiveMultiple sclerosis (MS) is an inflammatory demyelinating disease of the central nervous system (CNS). Myeloid phagocytes, including blood monocytes recruited to demyelinating lesions, may play a dual role in MS: on one hand, they might enhance CNS damage after differentiating toward a proinflammatory phenotype; on the other, they promote remyelination and repair through effective phagocytosis of myelin debris. We have previously determined that the retinoid X receptor (RXR) plays an important role in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
26
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 63 publications
2
26
1
Order By: Relevance
“…As outlined further above, it is known that myelin debris is a major obstacle to neurorepair both as a physicospatial impediment via the expression of axon growth inhibitory molecules and also via an inhibition of OPC differentiation (18,(37)(38)(39). In doing so, myelin debris inhibits remyelination (18) so that this microglial core ability has recently become a new target for potential therapeutic approaches (40,41). Moreover, we observed that pHERV-W ENV stimulation led to a pronounced morphological shift to ameboid microglial phenotypes typical of proinflammatory activation already apparent after 1 and 2 d of pHERV-W ENV stimulation ( Fig.…”
Section: Pherv-w Env Induces a Proinflammatory Phenotype In Culturedmentioning
confidence: 99%
“…As outlined further above, it is known that myelin debris is a major obstacle to neurorepair both as a physicospatial impediment via the expression of axon growth inhibitory molecules and also via an inhibition of OPC differentiation (18,(37)(38)(39). In doing so, myelin debris inhibits remyelination (18) so that this microglial core ability has recently become a new target for potential therapeutic approaches (40,41). Moreover, we observed that pHERV-W ENV stimulation led to a pronounced morphological shift to ameboid microglial phenotypes typical of proinflammatory activation already apparent after 1 and 2 d of pHERV-W ENV stimulation ( Fig.…”
Section: Pherv-w Env Induces a Proinflammatory Phenotype In Culturedmentioning
confidence: 99%
“…Monocytes are also involved but can play a dual role by promoting or resolving inflammation depending on their activation state. 1 Recent studies have shown that circulating monocytes in MS patients resemble classically activated monocytes, [2][3][4] and this classical activation state is found on both of the major monocyte subsets. 3 Monocytes can be divided into two well-characterized subsets CD14 ++ CD16 − and CD14 + CD16 + monocytes.…”
mentioning
confidence: 99%
“…The retinoid X receptor (RXR) plays an important role in monocyte/macrophage phagocytosis of myelin as suggested by pioglitazone-induced activation of peroxisome proliferatoractivated receptor c, one of the permissive binding partners of RXR, shown to inhibit pro-inflammatory differentiation of MS patient-derived monocytes/macrophages and to enhance myelin phagocytosis (Natrajan et al, 2015b). Moreover, the blockade of myelin debris clearance by microglia/macrophages in cuprizone-demyelinated CX3CR1-deficient mice, revealed the critical role played by CX3CR1, the receptor controlling microglial physiology and orchestrating the crosstalk between microglia and neurons (Lampron et al, 2015).…”
Section: The Critical Role Of Microglia/macrophages In Myelin Phagocymentioning
confidence: 99%